Application of CO2 waveform in the alveolar recruitment maneuvers of hypoxemic patients during one-lung ventilation. Issue 24 (June 2016) - Dong, Chunshan; Yu, Junma; Liu, Qi; Wu, Chao; Lu, Yao
Abstract : Abstract: Deterioration of gas exchange during one-lung ventilation (OLV) is caused by both total collapse of the nondependent lung and partial collapse of the dependent lung. Alveolar recruitment maneuver improves lung function during general anesthesia. The objective of this study was to investigate whether there is an indirect relationship between the changes of CO2 expirogram and the selective lung recruitment. To further improve the oxygenation and gas exchange, we compare adjust setting of ventilated parameters based on CO2 expirogram and a preset setting of ventilated parameters during OLV in patients undergoing right-side thoracic surgery. Thirty patients met the requirements criteria that were studied at 3 time points: during two-lung ventilation (TLV), during OLV with preset ventilation parameters (OLV-PP), and during OLV with adjustable ventilation parameters (OLV-AP) that are in accordance with CO2 expirogram. Adjustable ventilation parameters such as tidal volume (VT), respiratory rate (RR), positive end-expiratory pressure (PEEP), and the ratio of inspiratory to expiratory were adjusted by utilizing the phase III slopes of CO2 expirogram, which together with the relationship between the changes of CO2 expirogram and the selective lung recruitment. During OLV, the phase III slopes of CO2 expirogram in patients with pulse oxymetry (SpO2 ) decreased less than 93% after the OLV-PP, and were absolutely different from that during TLV. After OLV-AP, the phase III slopes of CO2 expirogram and SpO2 were similar to those during TLV. During OLV, however, parameters of ventilation setting in both OLV-PP and OLV-AP are obviously different. This study indicates that alveolar recruitment by utilizing CO2 expirogram probably improves SpO2 level during one-lung ventilation.